Permodelan Spasial Lahan Terbangun Menggunakan Spasial Statistik dan Penginderaan Jauh (Studi Kasus : Kota Batu, Jawa Timur) - Hana Sugiastu Firdaus (Elipsoida : Jurnal Geodesi dan Geomatika, 2018)
Batu City is one of the tourism cities in East Java Province which often visited by several tourists, so that is necessary to increase infrastructure development which causes land functions changes. The land use changes can be observed temporally by utilizing satellite imagery. In this study, Landsat 7 ETM + and Landsat 8 satellite imagery is used to map the land use in Batu City in 2006, 2009 and 2013, which later spatially processed using the mathematical Binary Logistic Regression method to obtain the built-up land modelling in the study area. The built-up land area has increased from 2006 until 2013, where in 2006 (10.26 km2) and in 2013 (17.69 km2). The results of change built-up land in Batu City using Binary Logistic Regression modelling for years 2006-2009 is : Y = 0.8028 + 0.0003 X1 + 0.0071 X2 -0.0418 X3 +0.0004X4, while change built-up land for years 2009-2013 in Batu City is Y = -0.6227 + 0.0008 X1 + 0.0025 X2 -0.0141 X3 +0.0002X4 +0.0103X5, which the predictor variable X1 is distance from collector roads, X2 (distance from local roads), X3 (distance from agriculture), X4 (distance from rivers), and X5 (distance from existing built-up land in 2009). Percentage of modelling accuracy for change built-up land in Batu City for years 2006 - 2009 is 76.53% and 71.69% for predict the change built-up land in 2009 - 2013. Whereas for modelling accuracy of change built-up land in Batu City for years 2009 - 2013 is 77.65%